(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Cephalic index is an important parameter for deciding the race and sex of an individual whose identity is unknown. In thepresent study we tried to work out Cephalic index in post graduate medical students of Maharashtra. 400 post graduate medical students were measured for head length and head breadth and cephalic index was worked out. Comparing previous records of cephalic index with recent work proves tendency towards “brachycephalisation” evidence of continuous growth of brain more in the lateral direction. The data collected by the authors will be of importance in anatomy, forensic medicine, anthropology and in genetics.